DÚ 3

Zjednodušte:

  1. \left(a-\dfrac{4ab}{a+b}+b \right):\left(\dfrac{a}{a+b}-\dfrac{b}{b-a} -\dfrac{2ab}{a^2-b^2} \right) =
  2. \dfrac{x}{ax-2a^2}-\dfrac{2}{x^2+x-2ax-2a}\cdot\left(1+\dfrac{3x+x^2}{3+x}\right) =
  3. \dfrac{2a}{a^2-4x^2}+\dfrac{1}{2x^2+6x-ax-3a}\cdot\left(1+\dfrac{3x-6}{x-2}\right) =
  4. \dfrac{3ab}{a^2-ab}+\dfrac{5a}{a+b}-2\cdot\dfrac{b^2+2a^2}{a^2-b^2}=
  5. \left(\dfrac{1}{2x-y}+\dfrac{3y}{y^2-4x^2}-\dfrac{2}{2x+y}\right):\left(\dfrac{4x^2+y^2}{4x^2-y^2}+1\right) =

Napsat komentář

Vaše emailová adresa nebude zveřejněna. Vyžadované informace jsou označeny *